Pelatihan Implementasi Pendekatan Onto-Semiotik dalam Pembelajaran di Kelas bagi Guru SMP Al-Bahjah Tulungagung - Dian Septi Nur Afifah (Universitas Mathla'ul Anwar Banten, 2019)
TRAINING ON THE IMPLEMENTATION OF ONTO-SEMIOTIC APPROACH IN CLASS LEARNING FOR TEACHERS AT JUNIOR HIGH SCHOOL AL-BAHJAH TULUNGAGUNG. The purpose of this community service activity is the teachers training by implementing an onto-semiotic approach in classroom learning and produce a lesson plan. This activity done at Junior High School Al-Bahjah Tulungagung. The participants are teachers in Junior High School Al-Bahjah Tulungagung. The method used is theory method and practice. The results obtained throught this training are knowldge of innovative learning with an onto-semiotic approach for teachers and their ability to create and implement the lesson plan with an onto-semiotic approach.